Road Transport Investment Projects and Additional Economic Benefits - Torben Holvad; John Preston (European Regional Science Association (ERSA), 2005)
The paper examines the linkages between transport and the economy with particular focus on the basis for additionality of wider economic benefits from road transport infrastructure improvements. A major weakness of current appraisal practice of road transport infrastructure projects is its basis on partial equilibrium analysis. The partial equilibrium approach implies that the linkage from changes in the transport market is ignored creating the scope for a less than comprehensive consideration of all benefits and costs. The importance of ignoring other markets in transport appraisal has been subject to much analysis in the available literature: A key research question is whether such wider economic impacts are additional to the time and cost savings generated from transport policy interventions. The key condition under which wider economic effects are additional to a standard CBA is the extent to which the economy departs from the economic model of perfect competition. If imperfect competition dominates then it is possible that the wider economic effects can be additional to the CBA result. The context in which perfect competition is not a valid assumption involves imperfectly competitive output and input markets and/ or existence of subsidies and taxes. Furthermore, external costs such as air pollution or congestion from the transport sector as well as from economic activities across the different sectors can influence the CBA result. Computable General Equilibrium (CGE) models represent a possible solution to the problem of partial equilibrium analysis. The paper will review available theoretical and empirical evidence of how road transport improvements are linked to the wider economy including the possibility for addditionality. It will re-assess the role of Computable General Equilibrium models in measuring these additional benefits. Finally, it will consider the feasibility of examining the additional benefits that Britain's motorway network has brought to the national economy.
Keywords: 330